Community-led Initiatives and the Social Solidarity Economy: Commons Ecologies for Delivering and Re-Imagining the Sustainable Development Goals. - Hefrey, T.; Esteves, A. M.; East, M.; Genus, A; Penha-Lopes, G (Community-led Initiatives and the Social Solidarity Economy: Commons Ecologies for Delivering and Re-Imagining the Sustainable Development Goals., 2019)
This paper examines how community-led initiatives are deploying social solidarity economy in distinctive ways as a vehicle for local action consistent with delivery of the Sustainable Development Goals. It employs the concept of commons ecologies to capture how such activities restructure relationships and interactions among SSE actors and organisations. Such interactions characterise both local and regional commons ecologies and participation of local and regional actors in wider networks at national, international and global levels. Case studies from UK, Portugal, Brazil and Senegal each illuminate different qualities of local/regional commons ecologies and their forms of engagement with wider networks. In each case, SSE acts as a vehicle for expressing participants’ values and principles consistent with those underlying the SDGs. Local implementation of SDGs is thus an inbuilt feature of these commons ecologies. Their participation in international and global networks offers opportunities for more mainstream processes to learn from local level experiences and successes, potentially strengthening SDG implementation more generally.